Variação populacional e comportamento alimentar de Mimus saturninus (Lichtenstein 1823) Polioptila dumicola (Vieillot 1817) e Saltator atricollis (Vieillot 1817) - Almeida, Caroline Gomes de (2009)
The monitoring of populations throughout the year provides information about how birds respond to seasonal variations of the environment. By their feeding behavior, it is also possible to understand how birds establish in the habitat. The objectives of this study were to verify if three species of birds that have different diets showed populational variation throughout the year. The species studied were Mimus saturninus, that is omnivorous, Polioptila dumicola is insectivorous and Saltator atricollis is granivorous. Moreover, the abundance of M. saturninus was compared between a preserved cerrado and an urban area. The foraging behavior of the three species was also featured. The study was developed at Reserva Ecológica Particular do Caça e Pesca and in Parque Municipal do Sabiá (Uberlândia, Minas Gerais). The weather in this region has two well-defined seasons, hot and rainy summer, and cold and dry winter. The stricto sensu cerrado is the dominant phytophisiognomy in Caça e Pesca reserve, in addition to palm swamp and forest. In Parque do Sabiá there are forests, palm swamp and gardens. The punctual abundance was estimated in transects with 20 points in each area, with 15 days intervals, during one year. Twenty points were distributed in two transects in Caça e Pesca, and 20 points in three transects in Parque do Sabiá. The feeding behavior observations of the species occurred during the end of the rainy and at the beginning of the dry season. Saltator atricollis was also observed during the dry season. Observations were conducted for attack behavior and location of foraging. The abundance of M. saturninus was higher in the Caça e Pesca than in the Parque do Sabiá, and did not vary between the dry and rainy seasons. The abundance of S. atricollis also did not differ significantly between the seasons because it was found high amount of individuals in the rainy season and the beginning of the dry season. Polioptila dumicola was recorded only during the rainy season at Caça e Pesca and at Parque do Sabiá was found with high frequency in the dry season. Mimus saturninus constantly forage on the ground in two areas and at Caça e Pesca it also consumed high proportion of fruits from shrubby and arboreous layer. Polioptila dumicola consumed mainly insects in the arboreous layer. Saltator atricollis fed predominantly in the herbaceous/ ground and shrubs layer, consuming mainly grains and flower buds. The species responded in different ways to seasonality. Mimus saturninus did not present populational variation between the seasons because its omnivorous diet allows a higher tolerance to the seasonal alterations of the food resources. Saltator atricollis was abundant in the rainy season and in the beginning of the dry season probably due to seasonal availability of fruits and grains. Polioptila dumicola also showed populational variation during the seasons. The abundance of resources of the cerrado in Caça e Pesca during the rainy season possibly favored the presence of the P. dumicola. This specie was abundant in the dry season in Parque do Sabiá due to insects availability in forest environments and other arboreous layers in the park.